PSVIII-B-5 Dynamic of Accessible Chromatin Regions in Cattle Rumen Epithelial Tissue During Weaning. (21st September 2022) - Boschiero, Clarissa; Gao, Yahui; Vi, Rannsom Baldwin; Liu, George E; Li, Congjun
Abstract: Weaning in ruminants is characterized by the transition from a milk-based diet to a solid diet which drives a critical gastrointestinal tract transformation. Identifying regulatory control of this transformation during weaning can help identify strategies to improve rumen health. This study aimed to identify regions of accessible chromatin in rumen epithelial tissue in pre- and post-weaning calves and investigate differentially accessible regions (DARs) to uncover regulatory elements in cattle rumen development using the ATAC-seq approach. A total of 126, 071 peaks were identified, covering 1.15% of the cattle genome. From these accessible regions, 2, 766 DARs were discovered. Gene ontology enrichment resulted in GO terms related to cell adhesion, anchoring junction, growth, cell migration, motility, and morphogenesis. In addition, putative regulatory canonical pathways were identified (TGFβ, Integrin-linked kinase, Integrin signaling, and regulation of the epithelial-mesenchymal transition). Canonical pathways integrated with co-expression results showed that TGFβ and ILK signaling pathways play essential roles in rumen development through the regulation of cellular adhesions. In this study, DARs during weaning have been identified, revealing enhancers, transcription factors, and candidate target genes that represent potential biomarkers for the bovine rumen development which will serve as a molecular tool for rumen development studies.